MASA KERJA, PEMAKAIAN ALAT PELINDUNG MATA, WAKTU PAPARAN DAN KETAJAMAN PENGLIHATAN PEKERJA BENGKEL LAS DI KOTA YOGYAKARTA - , AZIR ALFANAN, Prof. Dr. dr. Soebijanto, dr. Hartono, Sp. M(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Visual acuity is a problem of Occupational Safety and Health (OSH) in welding workshop. Eye protection equipment usage, illumination or lighting, exposure duration, working period, refractive error and age can affect visual acuity of welding workers. In Yogyakarta there were 15 welding workshops, which were mostly never carried out visual acuity check, they didnât know the visual acuity of their welding workers. Objective: This research aimed to protect the welding workers from low vision risk based on working period, eye protectection equipment usage, and exposure time. Methods: This research used analytic method with cross sectional design. The sampling technique which used was purposive sampling. Results: The results showed that, there were 65 respondents had normal visual acuity and 19 respondents who had already decreased their visual acuity. The analysis showed that there was negative correlation between working period with visual acuity (p = 0.000 and r = -0.574), there was difference in visual acuity between the respondents who used and who didnât use eye protection equipment (p = 0.000), there was negative correlation between exposure duration with visual acuity (p = 0.004 and r = -0.312), and eye protection equipment usage had most huge influence visual acuity error (coefficient Î² = 0,181). Conclusion: There was negative correlation between working period with visual acuity, there was difference of visual acuity between respondents who used eye protection equipment and them who didnât use, there was negative correlation between the exposure duration with visual acuity, and eye protection equipment usage had most huge influence visual acuity error.